Java threads and the concurrency utilities - Friesen, Jeff (Expert's voice in Java., 2015)
Threads and the Concurrency Utilities helps all Java developers master the complexity of Java's Thread APIs and Java's Concurrency Utilities. This knowledge aids the Java developer in writing correct and performant multithreaded applications. Everything you want to know about Java's support for threads and concurrency in one place. Chapter exercises designed to reinforce chapter content and help the reader retain knowledge. Lambdas, the try-with-resources statement, and other modern language features are present. Standard Class Library use of threads in Swing, JavaFX, and Java 8 Streams API contexts explained. The author Jeff Friesen is an accomplished Java expert, JavaWorld columnist, books author and much more.